DIBL enhancement in ferroelectric-gated FinFET. (7th January 2019) - Cho, Hyungki; Shin, Changhwan
Abstract: Drain-induced-barrier-lowering (DIBL) is one of short-channel-effects (SCEs) of conventional field effect transistors (FET), which results in lowering the threshold voltage of short-channel transistors. To properly control the DIBL of FinFETs, it is well known that the fin width of the FinFET can be adjusted (usually, a narrower fin width to enhance gate-to-channel coupling). In this work, the fin width effect of FinFETs (vs. ferroelectric-gated FinFETs, a.k.a., negative capacitance (NC) FinFETs) on the DIBL has been investigated and compared. As a result, it is experimentally verified that the NC-FinFET has superior gate-to-channel controllability and better subthreshold swing due to the negative capacitance effect of ferroelectric capacitor.